A bacterial symbiont and a plant virus enhance insect fitness by inducing physical defenses against fungal parasites - Tian-Yu Wang; Ji-Sheng Hong; Shuang-Xiu Song; Kai-Heng Wei; Nai-Fei Chen; Ling-Rui Li; Xi Jiang; Geng-Jun Zhong; Ze-Yu Ma; Yang Yang; Tian Liu; Chengshu Wang; et al. (Proceedings of the National Academy of Sciences, 2026)
Defensive symbioses in which beneficial microbes protect hosts from natural enemies are ubiquitous across animals and plants, but the underlying mechanisms remain poorly understood. Field surveys and laboratory assays revealed that infection of the invasive whitefly Bemisia tabaci by the bacterial symbiont Rickettsia and plant begomovirus were positively correlated with each other but each negatively correlated with a parasitic fungal infection ( Beauveria bassiana ) in the host. We show that begomovirus conferred whitefly’s resistance to the parasitic fungus by triggering the expression of chitin synthesis pathway genes in whiteflies, reinforcing the cuticle by promoting chitin production. The facultative symbiont Rickettsia facilitated cuticle formation and thereby induced physical defense against entomopathogenic fungus via metabolic cooperation with the obligate symbiont Portiera for the synthesis of phenylalanine and tyrosine in whiteflies, which is used to generate cuticular proteins and pigments. Mutation of chitinase and protease genes in B . bassiana impaired fungal infection of whiteflies. Inhibiting whitefly cuticle formation by repressing chitin and phenylalanine synthesis facilitated fungal infection. Thus, begomovirus and Rickettsia have convergent effects on cuticle defense in whiteflies by impacting distinct molecular pathways. Such defensive symbioses apparently contribute to B . tabaci fitness in the field and our findings reveal that interactions among the host, beneficial microbes, and pathogens have important implications for insect ecology and evolution. This study suggests avenues for pest management by leveraging defensive microbes and targeting the host cuticle.